The Croatian Health Insurance Fund Does Not Recognize Differences in the Cost of Different Treatments for Revision Total Hip Arthroplasty - Srećko Sabalić; Dinko Vidović; Slaven Babić; Tomislav Ćuti; Domagoj Gajski; Krešimir Rotim; Dejan Blažević (Acta Clinica Croatica, 2020)
In recent years, there has been increased interest in the cost of treatment for revision interventions for hip and knee prostheses. In all publications so far, the authors note the high cost of treatment for revision interventions, especially if infection is present. The aim of this study was to compare the cost of treatment and health insurance reimbursements between revision total hip arthroplasty (THA) for infection and revision for aseptic indications (aseptic instability and periprosthetic fracture). Hospital data on 168 patients having undergone revision THA between 2010 and 2018 at the Department of Traumatology, Sestre milosrdnice University Hospital Centre from Zagreb were analyzed. Financial data were collected from the Hospital Information System. Financial analysis included total cost per patient, Croatian Health Insurance Fund reimbursements, cost of implants, and length of hospital stay. The difference between the mean total cost per patient and the mean Croatian Health Insurance Fund reimbursements was -262.83 € (-6.08%) for aseptic instability, -1694.94 € (-17.25%) for infection and -916.49 € (-17.33%) for periprosthetic fracture. The Croatian Health Insurance Fund does not recognize differences in the cost of revision THA for aseptic instability, infection and periprosthetic fracture. Health insurance reimbursement is inadequate for centers that offer revision hip surgery.